2019
DOI: 10.1016/j.humov.2019.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Ankle dorsiflexion range of motion is associated with kinematic but not kinetic variables related to bilateral drop-landing performance at various drop heights

Abstract: 25Limited evidence is available concerning ankle dorsiflexion range of motion (DF ROM) and 26 its relationship with landing performance from varying drop heights. The aim of this 27 investigation was to determine the relationship between ankle DF ROM and both kinetic and 28 kinematic variables measured during bilateral drop-landings from 50%, 100% and 150% of 29 countermovement jump height. Thirty-nine participants were measured for their ankle DF 30 ROM using the weight-bearing lunge test, after which five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
1
29
1
Order By: Relevance
“…12 Consistent with this suggestion, several studies have reported no relationship between ankle mobility and landing forces. [12][13][14] However, ankle DF ROM measured using the weight-bearing lunge test (WBLT), is related to ankle dorsiflexion (r = -0.31 to -0.34) and knee flexion (r = -0.37 to -0.41) angles at initial contact during bilateral drop-landings from drop heights equating to 100% and 150% of countermovement jump (CMJ) height in recreational athletes. 12 In the same investigation, significant relationships were also found between ankle DF ROM and peak ankle dorsiflexion (r = -0.43 to -0.44), knee flexion (r = -0.42 to -0.52) and frontal plane projections angles (FPPA) (r = 0.37) at the moment of peak knee flexion during bilateral drop-landings.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…12 Consistent with this suggestion, several studies have reported no relationship between ankle mobility and landing forces. [12][13][14] However, ankle DF ROM measured using the weight-bearing lunge test (WBLT), is related to ankle dorsiflexion (r = -0.31 to -0.34) and knee flexion (r = -0.37 to -0.41) angles at initial contact during bilateral drop-landings from drop heights equating to 100% and 150% of countermovement jump (CMJ) height in recreational athletes. 12 In the same investigation, significant relationships were also found between ankle DF ROM and peak ankle dorsiflexion (r = -0.43 to -0.44), knee flexion (r = -0.42 to -0.52) and frontal plane projections angles (FPPA) (r = 0.37) at the moment of peak knee flexion during bilateral drop-landings.…”
Section: Introductionmentioning
confidence: 82%
“…3 However, restrictions in ankle dorsiflexion range of motion (DF ROM) can negatively influence the coordination of the proximal segments during landings by imposing a mechanical organismic constraint that can limit an individual's capacity to adopt effective movement strategies. [11][12][13][14] It is therefore possible that reduced ankle DF ROM contributes to the development of compensatory strategies throughout the lower extremity in an attempt to maintain peak vGRF below an intolerable threshold. 12 Consistent with this suggestion, several studies have reported no relationship between ankle mobility and landing forces.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations